Threads of hope : counselling and emotional support services for communities in crisis - Dale, Susan (Cambridge Scholars Publishing, 2016)
On 1st October 2012, April Jones, aged 5, was abducted from outside her home in the small Welsh market town of Machynlleth. This led to the largest police search operation of its kind ever conducted in the UK, and a subsequent murder investigation and trial which was scrutinised by the international media.This book uses a collaborative narrative research process to explore the lived experiences of one specific group of community members who responded to this event by setting up, and running, a therapeutic project to support the community between 2012 and 2014.The author weaves together threads.